Analysis of the contribution of the Youth Livelihood Program towards enhancing Self-Reliance among the Youths in Lira City, Uganda - Achiro, Elizabeth Dorky; Mwesigwa, David (Journal of Social, Humanity, and Education, 2023)
Purpose: This study investigated the contribution of the YLP towards enhancing self-reliance among the youths in the west division of Lira City. Methodology/approach: The study employed a descriptive cross-sectional design. A closed-ended structured questionnaire with a five Likert scale was used to collect data from a sample of 249 respondents based on the program theory postulated by Reynolds (1998); it entails the logic behind how programs are built, with particular emphasis on the program process. Data were analyzed using both descriptive statistics and inferential statistics aided by SPSS (version 20).  Results: The findings suggested that the YLP program enhanced self-reliance among the youths by 11.1%. The youths in Lira City West Division moderately benefited from livelihood support (3.10, SD = 1.08) and institutional support (Mean = 2.71, SD = 1.241). A robust regression analysis revealed a positive and significant relationship between the YLP program and self-reliance (R2 = 0.111). Livelihood support (Coef = 0.159, p-value 0.0025) was found to be positively and significantly correlated with self-reliance. However, the statistical analysis revealed that institutional support had a negative relationship with self-reliance (p-value > 0.05, 95% CI).  Limitations: During the study, it was difficult to find some respondents since they were scattered looking for activities to earn a living therefore extra efforts were ensured such as using research assistants in order to find the respondents. Inadequate funds to facilitate the study like transport to the field, and printing questionnaires were also a problem. The researcher got a loan from friends and the bank to cover the gap. Contributions: This study contributes to the understanding of local community development initiatives using the empowerment approach.